2016
DOI: 10.4314/ahs.v16i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human endostatin reduces hypertrophic scar formation in rabbit ear model through down-regulation of VEGF and TIMP-1

Abstract: Background: Recombinant human endostatin (Endostar) has been widely used to suppress angiogenesis in carcinoma patients. Hypertrophic scar (HS) tissue, much like a carcinoma, is often associated with angiogenesis. However, there have been few studies conducted on the effects of Endostar on HS or its mechanism. Objective: This paper investigated the effects Endostar on the HS of rabbit ears and studied the effects of Endostar on VEGF and TIMP-1 expression. Methods: Sixteen New Zealand white rabbits were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…Vascular endothelial growth factor (VEGF), which is produced by epidermal cells, is a positive regulator of angiogenesis. Because of this, overexpression of VEGF is related to excessive capillary formation, collagen type I production and overall scar volume increase [ 9 ]. These cytokines are not only fibrogenic growth factors, but also chemotactic agents for epithelial cells, endothelial cells, neutrophils, macrophages, mast cells and fibroblasts [ 4 , 8 ].…”
Section: Important Proteins and Cytokines In The Wound Healing Promentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF), which is produced by epidermal cells, is a positive regulator of angiogenesis. Because of this, overexpression of VEGF is related to excessive capillary formation, collagen type I production and overall scar volume increase [ 9 ]. These cytokines are not only fibrogenic growth factors, but also chemotactic agents for epithelial cells, endothelial cells, neutrophils, macrophages, mast cells and fibroblasts [ 4 , 8 ].…”
Section: Important Proteins and Cytokines In The Wound Healing Promentioning
confidence: 99%
“…Fibroblasts originating in keloid tissues show increased receptors to these growth factors and demonstrate increased responsiveness compared with fibroblasts from normal tissues [ 10 , 11 , 12 , 13 ]. Tissue inhibitors of metalloproteinases (TIMPs) are endogenous inhibitors of matrix metalloproteinases (MMPs); thus, increased levels of TIMPs, especially TIMP-1 and TIMP-2, are associated with hypertrophic scar formation [ 9 ]. Tumor necrosis factor-α (TNF-α) is an inflammatory cytokine produced by monocytes and macrophages during the inflammatory phase.…”
Section: Important Proteins and Cytokines In The Wound Healing Promentioning
confidence: 99%
“…Notably, two recent studies demonstrated that topical application and intralesional injection of bevacizumab, a monoclonal antibody directed against VEGF, partially prevent the formation of hypertrophic scars in rabbit models of impaired wound healing. [ 22,23 ] Similar results were observed following treatment of pathological wounds with endostatin, which down‐regulates VEGF expression, [ 24 ] as well as with adenoviral vectors encoding a matrix metalloproteinase known to sequestrate VEGF‐165. [ 25,26 ] Our results suggest, however, that the vascular dysfunction observed in hypertrophic scarring may not be exclusively mediated by cell‐to‐cell interactions involving classical paracrine exchanges of soluble VEGF or other cytokines.…”
Section: Discussionmentioning
confidence: 55%
“…MV production was quantified by autofluorescence emission spectra analysis as previously described. [7] Briefly, after 24…”
Section: Quantification Of Mvs By Flow Cytometrymentioning
confidence: 99%
“…93 The activity of Endostar is mediated by antagonizing the VEGF pathway. 94,95 In addition, in rabbit scar models, Endostar reportedly attenuates the formation of HS by inhibiting the expression of VEGF and TIMP-1 94 and downregulates dermal fibroblast proliferation via G 0 /G 1 and/or G 2 /M phase cell cycle arrest. 96 Although a few publications have reported outcomes of the clinical application of Endostar for the management of HS, we look forward to the results of this promising therapeutic modality.…”
Section: Challenges Of Traditional Therapies and The Potential Of Vascularand Collagen-targeted Therapiesmentioning
confidence: 99%